The impact of helicopter parenting on grit and mental well-being among university students - Ernawati; Kusumawardhani, Sri Juwita; Mayangsari, Anggi; Sari, Salsabila Mayang; Adhiningtyas, Nanda Putri (University of Muhammadiyah Malang, 2026)
University students experience increasing academic and developmental demands that require psychological resources to support persistence and well-being. Parenting experiences, particularly helicopter parenting characterized by excessive parental involvement and control, may influence these psychological outcomes. This study aimed to examine the impact of helicopter parenting on grit and mental well-being among university students. Using a non-experimental quantitative design, data were collected from 324 undergraduate students aged 17 to 29 years who resided on the island of Java. Participants completed measures of helicopter parenting, grit, and mental well-being. Data were analyzed using descriptive statistics and simple linear regression with a bootstrapping procedure to obtain robust estimates. The results showed that helicopter parenting had a statistically significant but weak negative impact on grit, indicating that higher parental overinvolvement was associated with slightly lower perseverance and consistency of effort. In contrast, helicopter parenting did not show a significant impact on mental well-being. These findings suggest that helicopter parenting influences specific motivational traits rather than overall psychological well-being. This study highlights that the impact of helicopter parenting among university students is limited and domain-specific, emphasizing the importance of examining distinct psychological outcomes when evaluating parenting influences during emerging adulthood.